ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RISK PROFILE, EARNINGS AND CAPITAL (Studi pada PT. Bank Mandiri (Persero) Tbk. Periode 2013–2016) - Ryan Hafidhin; Sri Mangesti Rahayu; Zahroh Z.A Zahroh Z. A (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This study uses three (3) the assessment factors in analyzing the health of banks, including factors Risk Profile (Risk Profile) with the NPL ratio and the LDR, Earning factors (profitability) with ROA and NIM, factors Capital (Capital) with CAR. GCG factors not analyzed because it involves the bank secrecy. The method used in this research is descriptive method with quantitative approach. Location of research conducted at PT Bank Mandiri (Persero) Tbk. listed on the Indonesia Stock Exchange (BEI). The results showed that PT Bank Mandiri (Persero) Tbk. as the government-owned bank that has the greatest asset, measured by the ratio of NPL, LDR, ROA, NIM and CAR gain Composite Rating 1 with the title of